F. Scott Fitzgerald's The great Gatsby - Bloom, Harold (Philadelphia : Chelsea House, 2004)
Presents critical essays on F. Scott Fitzgerald's "The Great Gatsby" and includes a chronology, a bibliography, and an introduction by critic Harold Bloom.
The great Gatsby : two versions of the hero / David Parker -- Gatsby and the failure of the omniscient "I" / Ron Neuhaus -- Gatsby and John Keats : another version / Joseph B. Wagner -- The waste land myth and symbols in The great Gatsby / Letha Audhuy -- Compensating visions : The great Gatsby / John T. Irwin -- The great Gatsby : Fitzgerald's opulent synthesis (1925) / Robert Roulston and Helen H. Roulston -- Individualism reconsidered / Ronald Berman -- "A world complete in itself" : Gatsby's elegiac narration / Dan Coleman -- "An elusive rhythm" : The great Gatsby reclaims Troilus and Criseyde / Casie Hermansson -- Implying authors in The great Gatsby / Elizabeth Preston -- Carraway's complaint / George Monteiro -- Possessions in The great Gatsby / Scott Donaldson.
Includes bibliographical references (p. 213-216) and index.
Young Adult
Keywords: Fitzgerald, F. Scott -- 1896-1940.